2022
DOI: 10.1177/20584601221131481
|View full text |Cite
|
Sign up to set email alerts
|

Myxomas and myxoid liposarcomas of the extremities: Our preliminary findings in conventional, perfusion, and diffusion magnetic resonance

Abstract: Background The differentiation between myxomas and myxoid liposarcomas (MLPS) often is a serious challenge for the radiologists. Magnetic resonance imaging (MRI) is the most useful imaging technique in characterization of the soft tissue tumors (STT). Purpose To evaluate in a sample of myxomas and MLPS of the extremities, what morphological findings in conventional MRI allow us to differentiate these two types of myxoid tumors, in addition to analyzing the validity of the apparent diffusion coefficient (ADC) v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Recent studies show that the evaluation of ADC values in DWI is useful to distinguish benign myxomas from myxoid liposarcomas, where higher ADC values support a more benign lesion. 5,9,16 Nuclear medicine has a limited role in intramuscular myxoma imaging with the majority of findings described on MRI. There is, however, mild to moderate F18-FDG avidity on PET-CT. 11 The most common complication of surgical excision of the myxomas is recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that the evaluation of ADC values in DWI is useful to distinguish benign myxomas from myxoid liposarcomas, where higher ADC values support a more benign lesion. 5,9,16 Nuclear medicine has a limited role in intramuscular myxoma imaging with the majority of findings described on MRI. There is, however, mild to moderate F18-FDG avidity on PET-CT. 11 The most common complication of surgical excision of the myxomas is recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Yabuuchi et al ( 9 ) showed that the apparent diffusion coefficient (ADC) decreased more in malignant phyllodes tumors than in benign phyllodes. Myxoid liposarcoma in the extremities also shows a lower ADC value than myxoma ( 10 ). Thus, both myxoid liposarcomas and phyllodes tumors are likely to have low ADC values.…”
Section: Discussionmentioning
confidence: 99%
“…53,54 However, of solid soft tissue tumors with high T2-weighted SI, authors have reported discrepant results on the efficacy of DWI and ADC mappings in differentiating benign from malignant myxoid soft tissue tumors, a particular histology to be aware of when assessing tumors with DWI. 40,[54][55][56][57][58] The assessment of treatment response in MSK lesions can benefit from DWI. 59,60 After chemotherapy or radiotherapy, neoplastic tissues typically lose cellularity and undergo necrosis or sclerosis.…”
Section: Functional Sequencesmentioning
confidence: 99%